The Effect of Word-of-Mouth and Celebrity Endorsement on Customer Satisfaction, with Marketing Strategy as an Intervening Variable, Among Customers of Oemah JM Coffee Shop in Jakarta - Dirgantoro, Jeremia Dewanto Pradana (Journal Research of Social Science, Economics, and Management, 2026)
The rapid growth of the coffee shop industry in Indonesia has intensified competition, requiring businesses to implement effective marketing strategies to enhance customer satisfaction. Factors such as word of mouth and celebrity endorsement are considered influential in shaping consumer perceptions and behaviors, particularly when supported by appropriate marketing strategies. The purpose of this study is to identify and analyze the effects of the variables word of mouth and celebrity endorsement on the customer satisfaction variable, with marketing strategy as an intervening variable. This research method employs multiple linear regression analysis, with data filtered using normality, multicollinearity, and autocorrelation tests. The results of the study show that each variable—word of mouth, celebrity endorsement, and marketing strategy—has a significant influence on the customer satisfaction variable. Meanwhile, the marketing strategyvariable is also significantly influenced by the word of mouth and celebrity endorsement variables. The role of word of mouth in this study is to form positive value perceptions through the use of buzzers and social media, while the role of celebrity endorsement is to create emotional engagement and pleasant experiences.